Original paperAcute complications following intracavitary high-dose-rate brachytherapy in uterine cancer - Gupta, Phalguni; Aich, Ranen Kanti; Deb, Asit Ranjan (Journal of Contemporary Brachytherapy, 2014)
Purpose: Almost 30% of malignancies in women of developing countries are gynecological and brachytherapy is an integral part of management of these patients. Reports of complications (both acute and late) of high-dose-rate (HDR) intracavitary brachytherapy are sparse in world literature due to relatively small number of gynecological malignancies, particularly in advanced stage, in developed countries. High-dose-rate brachytherapy is gaining popularity in developing countries due to scientific and economic reasons. Here we are reporting our experience regarding acute complications of intracavitary brachytherapy (events occurring within 30 days of insertion needing hospitalization or death) and their causes to improve the quality of management, so that the already low incidence of acute complications can be further reduced. Material and methods : From February 2004 to December 2012, a total of 1947 patients with uterine cancer were treated by HDR intracavitary brachytherapy in the Department of Radiotherapy, of a tertiary cancer centre of a developing country, 86% of them were cervical cancer and 14% endometrial cancer. Excluding the post-operative patients, a total of 4285 insertions were done in 1527 patients with intact uterus (eligible for analysis) and acute complications were analyzed. Results: Out of 4285 intracavitary brachytherapy insertions in gynecological malignancy patients, only 12 mortality and 239 morbidity instances needing hospitalization were documented and most of them were in cervical carcinoma patients. Conclusions : Our results have indicated that acute complications can be minimized by pre-treatment management of co-morbidities, decreasing the time of operative lithotomy position and bed rest, avoidance of ‘conscious sedation’ in selected cases etc. Routine post insertion CT scan if done in all patients in all insertions, then only, uterine perforations can be detected early and prompt management can reduce both the mortality and morbidity to a great extent.